2016
DOI: 10.1002/lsm.22537
|View full text |Cite|
|
Sign up to set email alerts
|

Transcutaneous temperature controlled radiofrequency for orgasmic dysfunction

Abstract: Background and ObjectivesTo evaluate the safety, tolerability, and clinical efficacy of transcutaneous temperature controlled radiofrequency (TTCRF) on vulvovaginal tissue for orgasmic dysfunction.Study Design/Materials and MethodsSubjects included 25 sexually active women, ages 21–65, with self‐reported difficulty in achieving orgasms during sex (anorgasmic or slow‐to‐orgasm). Each patient received three sessions at intervals of about 1 month. Treatment was performed using a slim S‐shaped probe with a stamp‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 6 publications
2
42
0
2
Order By: Relevance
“…Subjective patient reports All studies used subjective patient reports, but there was little consistency between them. Vaginal laxity improved in five studies, [83][84][85][86][87][88] and this effect lasted up to 6 months in 87% of patients. 87 Vaginal lubrication improved in one study 89 after one treatment and lasted up to 9-12 months.…”
Section: Temperature-controlled Radiofrequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective patient reports All studies used subjective patient reports, but there was little consistency between them. Vaginal laxity improved in five studies, [83][84][85][86][87][88] and this effect lasted up to 6 months in 87% of patients. 87 Vaginal lubrication improved in one study 89 after one treatment and lasted up to 9-12 months.…”
Section: Temperature-controlled Radiofrequencymentioning
confidence: 99%
“…87 Vaginal lubrication improved in one study 89 after one treatment and lasted up to 9-12 months. Sexual function scores improved compared to baseline [83][84][85][86][87][88]90 and lasted in one study up to 6 months post-treatment. 87 Alinsod 85 reported all anorgasmic patients (n = 10) achieved orgasm after receiving RF treatment.…”
Section: Temperature-controlled Radiofrequencymentioning
confidence: 99%
“…Radiofrequency devices have also been described in the treatment of other conditions, such as sexual dysfunction or vaginal laxity . Studies have also reported on its benefit in orgasmic dysfunction …”
Section: Indications and Evidence For Usementioning
confidence: 99%
“…35 Studies have also reported on its benefit in orgasmic dysfunction. 22 The age of women requesting these treatments depends on the indication. Treatment for GSM is in the menopausal age group but can be requested by younger women who have become menopausal following cancer treatment.…”
Section: Lichen Sclerosis Sexual Function and Vulval Conditionsmentioning
confidence: 99%
“…Através do aumento da temperatura, a radiofrequencia estimula a prodção de novos colagenos, fazendo com que a regiao vaginal modifique suas caracteristicas melhorando a função sexual, principalmente nos desfechos de dor na relação e dificuldade para atingir o orgasmo 18,19,20 .…”
Section: Conflitos De Interessesunclassified